PENGARUH PENERAPAN TEKNIK PEMBELAJARAN TRI FOKUS STEVE SNYDER TERHADAP PENINGKATAN KEMAMPUAN MEMBACA EFEKTIF - Rizka Maya Sari (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
This study aimed to determine the effect of learning techniques Tri Focus Steve  Snyder  to  improved  reading  skills  effectively.  The  population  in  this research were 260 students of class X SMA Negeri 1 Talawi Coal District. The sample  in  this  study  amounted  to  43  people  were  taken  to  probaliti  techniques. The instruments used to collect the data is an essay test. The method used in this study  is  a  quasi-experimental  or  quasi  experiment.  Of  processing  the  data obtained with the pre test mean = 63.13, standard deviation = 7.23. The results of the  post-test  mean  =  81.04,  standard  deviation  =  7.43,  then  didapatlah  t0  at 11.26.  Furthermore t0 is  known,  then  consulted  with  ttabel  at  5%  significance level with df = n-1 = 43-1 = 42. df = 42 obtained from the level of significance of 5%  =  2.02.  Because t0 obtained  greater  than  ttable  ie  19.88>  2.02,  the  null hypothesis  (Ho)  is  rejected  and  the  alternative  hypothesis  (Ha)  is  accepted. Concluded that there is a significant influence on the use of learning techniques Tri Focus Steve Snyder to improved reading skills effectively 2nd semester class X SMA  Negeri  1  Talawi  District  Coal  learning  year  2009/2010.Keywords : Learning Techniques Tri Focus Steve Snyder, Effective Reading